Implementasi Program Prolanis Terhadap Pengendalian Gula Darah Pasien Diabetes Pada Lansia Dirumah Kepala Desa Pupus - Delima; Anisah Qothrun Nada; Gelin Perista Elnada; Abdul Jakir; Muhammad Joko Sutrisno; Fauzan Masykur (MIKIR : Mathematics, Informatics, Knowledge And Information Research, 2025)
Diabetes mellitus is a chronic disease commonly found among the elderly and requires continuous management to prevent complications. The Chronic Disease Management Program implemented at the Head of Pupus Village’s residence, Ngebel District, Ponorogo Regency, was designed to support older adults in maintaining blood glucose levels through structured activities. This study aimed to evaluate the implementation of the program and its impact on blood glucose control among elderly patients with diabetes. A descriptive quantitative approach was applied, involving 30 respondents who actively participated in the program. Data were collected using questionnaires and blood glucose examinations, then analyzed descriptively and bivariately. The findings revealed that most respondents regularly attended the program, adhered to dietary recommendations, engaged in physical activity, and took medication as prescribed by health workers. As many as 56.7% of the elderly managed to maintain controlled blood glucose levels, while 43.3% remained unstable. These results indicate that the program has a positive impact on diabetes management among older adults, although further efforts are needed, including strengthening health education, involving families, and providing continuous assistance. Overall, the program implementation can be considered effective, but optimization is still required to ensure more equitable outcomes among all participants.